Transcatheter aortic valve replacement and standard therapy in inoperable patients with aortic stenosis and low EF. Issue 6 (13th January 2015) - Passeri, Jonathan J; Elmariah, Sammy; Xu, Ke; Inglessis, Ignacio; Baker, Joshua N; Alu, Maria; Kodali, Susheel; Leon, Martin B; Svensson, Lars G; Pibarot, Philippe; Fearon, William F; Kirtane, Ajay J; et al.
Abstract : Objectives: The aims of this study were to evaluate the effect of left ventricular (LV) dysfunction on clinical outcomes after transcatheter aortic valve replacement (TAVR) and standard therapy for severe aortic stenosis (AS) and to assess LV ejection fraction (LVEF) recovery and its impact on subsequent clinical outcomes. Methods: Cohort B of the Placement of AoRtic TraNscathetER Valves trial randomised 342 inoperable patients with severe AS to TAVR or standard therapy. We defined LV dysfunction as an LVEF <50% and LVEF improvement as an absolute increase in LVEF ≥10% at 30 days. Results: Baseline LV dysfunction did not affect survival after TAVR but was associated with increased cardiac mortality at 1 year with standard therapy (59.3% vs 45.8% with normal LVEF; HR=1.71 (95% CI 1.08 to 2.71); p=0.02). In those with LV dysfunction, LVEF improvement occurred in 48.7% and 30.4% of TAVR and standard therapy patients, respectively (p=0.08), and was independently predicted by relative wall thickness and receipt of TAVR. LVEF improvement with standard therapy portended reduced all-cause mortality at 1 year (28.6% vs 65.6% without LVEF improvement; HR=0.32 (95% CI 0.11 to 0.93); p=0.03) but not at 2 years. Conclusions: In inoperable patients with severe AS, mild-to-moderate LV dysfunction is associated with higher cardiac mortality with standard therapy but not TAVR. A subset of patients undergoing standard therapy with LV dysfunction demonstrates LVEF improvement and favourable 1-year but not 2-year survival. TAVR improves survival and should be considered the standard of care for inoperable patients with AS and LVEF >20%. Trial registration number: ClinicalTrials.gov Unique Identifier #NCT00530894 .